2015
DOI: 10.2337/db15-0478
|View full text |Cite
|
Sign up to set email alerts
|

High-Fat Diet During Mouse Pregnancy and Lactation Targets GIP-Regulated Metabolic Pathways in Adult Male Offspring

Abstract: Maternal obesity is a worldwide problem associated with increased risk of metabolic diseases in the offspring. Genetic deletion of the gastric inhibitory polypeptide (GIP) receptor (GIPR) prevents high-fat diet (HFD)-induced obesity in mice due to specific changes in energy and fat cell metabolism. We investigated whether GIP-associated pathways may be targeted by fetal programming and mimicked the situation by exposing pregnant mice to control or HFD during pregnancy (intrauterine [IU]) and lactation (L). Mal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
0
10
0
Order By: Relevance
“…In 6month-old mice exposed to a high-fat diet, the hypothalamic phosphorylation of mTOR ser2448 is decreased significantly in GIPR À/À mice. Further downstream, phosphorylation of S6kinase thr389 is nonsignificantly reduced, while its target protein S6 ser235/236 again shows significantly reduced phosphorylation [54]. At the transcript level, hypothalamic phosphatidylinositol 3-kinase mRNA is decreased in GIPR À/À mice, again supporting hypothalamic actions of GIP.…”
Section: Central Hypothalamic Akt-signal Pathway Regulated By Gipmentioning
confidence: 84%
See 2 more Smart Citations
“…In 6month-old mice exposed to a high-fat diet, the hypothalamic phosphorylation of mTOR ser2448 is decreased significantly in GIPR À/À mice. Further downstream, phosphorylation of S6kinase thr389 is nonsignificantly reduced, while its target protein S6 ser235/236 again shows significantly reduced phosphorylation [54]. At the transcript level, hypothalamic phosphatidylinositol 3-kinase mRNA is decreased in GIPR À/À mice, again supporting hypothalamic actions of GIP.…”
Section: Central Hypothalamic Akt-signal Pathway Regulated By Gipmentioning
confidence: 84%
“…However, the intrauterine and postnatal exposure of GIPR À/À mice to a high-fat diet abolishes this protection, leading to similar obesity and insulin resistance upon exposure to a high-fat diet after 6 month as in control mice. The intrauterine programming involves changes in hypothalamic phosphorylation and mRNA expression of the AKT-signaling pathway, as described above [54]. The most striking alterations are observed in enzymes involved in increased fat oxidation in skeletal muscle cells, which do not express GIPRs.…”
Section: Gip and Metabolic Programmingmentioning
confidence: 97%
See 1 more Smart Citation
“…However, pigs are encouraged to eat high‐fat diets once born, and therefore, it may be suggested that their mothers may offer some kind of protection for their foetuses, as high‐fat diets during pregnancy in other mammalian and human studies seem to have only negative consequences for metabolic disease risk (Khan et al ., ; Srinivasan et al ., ; Elahi et al ., ). An important recent study in mice has also shown that high‐fat diets during both gestation and lactation result in insulin resistance and obesity in the offspring, with increased inflammation originating in the adipose tissue (Kruse et al ., ). An observation confirmed a background of genetic deletion of gastric inhibitory polypeptide receptor (GIPR) that has previously been shown to prevent high‐fat diet‐induced obesity (Kruse et al ., ).…”
Section: Emergence Of Evidence For Skeletal Muscle Memorymentioning
confidence: 97%
“…An important recent study in mice has also shown that high‐fat diets during both gestation and lactation result in insulin resistance and obesity in the offspring, with increased inflammation originating in the adipose tissue (Kruse et al ., ). An observation confirmed a background of genetic deletion of gastric inhibitory polypeptide receptor (GIPR) that has previously been shown to prevent high‐fat diet‐induced obesity (Kruse et al ., ). However, if prenatal high‐fat diets are followed by normal diets consumed after pregnancy, it seems that offspring may not develop obesity but type II diabetes via increased cytokine activation, inflammation and mitochondrial dysfunction (Latouche et al ., ).…”
Section: Emergence Of Evidence For Skeletal Muscle Memorymentioning
confidence: 97%